Improper disposal of face masks during COVID-19: unheeded public health threat - Shiferie, Fisseha (Pan Afr Med J, 2021)
Ethiopia confirmed its first case of the novel coronavirus (COVID-19) pandemic in March 2020. As a means to tackle the spread of the virus, the government opened a campaign for the public to exercise hygiene measures such as washing hands frequently and physical distancing. A few weeks later, a five-month State of Emergency (SOE) was declared, and several businesses, schools and theatre halls were closed. People were advised to work from home, including permitting telecommuting for many government officials. However, mainly due to fear of economic crisis, the government was forced to release the lockdown and mass wearing of face masks has become a requirement. As health professionals and the government insist that people make use of facemasks, it is also equally important to give guidance on how to dispose of them safely because face masks that are disposed improperly have the potential in spreading SARS-CoV-2. The urgency of this comes in people's violations of rules when it comes to disposing of masks they used. Providing awareness creation programs about the negative impact of contaminated face masks on the health of individuals and introducing laws that can prohibit improper disposal of used personal protective equipment (PPEs) are among the solutions discussed in this manuscript that could help reduce the problem.